PERAN KEPUASAN KONSUMEN DALAM MEMEDIASI CUSTOMER VALUE DAN CUSTOMER EXPERIENCE TERHADAP LOYALITAS PELANGGAN (Studi Pada Pelanggan di Konter Bintang Phone Cell) - Widyakto, Adhi; Rachmawati, Dyah Ayu; Riyanto, Sugeng; Susanto, Susanto (JURNAL ILMIAH EDUNOMIKA, 2024)
This research aims to examine and analyze the influence of Customer Value and Customer Experience on Customer Loyalty through Customer Satisfaction as an intervening variable for customers at the Bintang Phone Cell Counter. The dependent variable used in this research is Customer Satisfaction (Z), Customer Loyalty (Y), while the independent variables used are Customer Value (X1) and Customer Experience (X2). The sample in this study was 96 respondents. The sampling technique uses purposive sampling with the criteria being that the respondent is at least 18 years old and has made at least 2 purchases. The analytical methods used are Convergent Validity, Discriminant Validity, Composite Reliability, Inner model. The results of the research conducted show that Customer Value and Customer Experience have a positive and significant effect on Customer Satisfaction, the Customer Value and Customer Experience variables have a negative and insignificant effect on Customer Loyalty, the Customer Value variable has a positive and significant effect on Customer Loyalty through Customer Satisfaction, and The Customer Experience variable has a positive and significant effect on Customer Loyalty through Customer Satisfaction